Behavioral problems in children with epilepsy - Dora Novriska; Retno Sutomo; Amalia Setyati (Indonesian Pediatric Society, 2014)
Background Epilepsy is a neurological disorder that most oftenaffects children. Most cases of epilepsy are found in developingcountries. Children with epilepsy are at risk of behavioral disordersthat can affect their quality of life. Studies on behavioral problemsin children with epilepsy have been limited in Indonesia.Objective To compare behavioral disorders in children withepilepsy to those in normal children, and to assess for possiblefactors associated with the occurrence of behavioral disorders.Methods We conducted a cross-sectional study involving 47children with epilepsy and 46 children without epilepsy, aged 3-16years. Behavioral problems were screened with the Strength andDifficulty Questionnaire (SDQ), Indonesian version. Informationabout EEG description, medication, onset, and duration of epilepsywere obtained from medical records.Results Behavioral problems were found in 19.1% of childrenwith epilepsy and only in 2.2 % of children without epilepsy (PR8.8; 95%CI 1.16 to 66.77; P= 0.015). Significant differences werealso found in the percentage of conduct problems and emotionaldisorders. Multivariate analysis with logistic regression revealedthat the factors associated with behavioral disorders in childrenwith epilepsy were uncontrolled epilepsy (PR 13.9; 95%CI 1.45 to132.4; P=0.023) and focal EEG appearance (PR 19; 95%CI 1.71to 214.43; P=0.017). We also found that uncontrolled epilepsywas a factor related to emotional (PR 6.7; 95%CI 1.66 to 26.76;P=0.007) and conduct problems (PR 6.1; 95%CI 1.35 to 27.29;P=0.019).Conclusion Uncontrolled epilepsy and focal EEG results arefactors associated with increased risk of behavioral problems inchildren with epilepsy. Children with epilepsy should undergobehavioral disorder screening, followed by diagnosis confirmationand treatment.